The Effect of Firm Size, Return On Equity, And Leverage on Firm Value - Nabila Nurmalitasari; Ngurah Pandji Mertha Agung Durya (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The company was formed with the aim of achieving profit or profit and prospering company owners and shareholders in an industry. The company not only has economic obligations to shareholders, but also has obligations to other interested parties and has a major influence on the establishment of the company. This study aims to analyze the effect of firm size, Return On Equity, and leverage on firm value. This study uses the independent variables of firm size, Return On Equity (ROE), and Leverage (DER) and the dependent variable is firm value (PBV). This study uses a purposive sampling method and the number of samples is 80 manufacturing companies with 4 years of research listed on the Indonesia Stock Exchange for the 2017-2020 period. The results of the study stated that Return On Equity (ROE) had an effect on firm value. Meanwhile, firm size and leverage have no effect on firm value.